Measuring integrity: A portrait of Gorontalo’s readiness to realize an integrity-driven governance system - Rio Monoarfa; Arip Mulyanto; Arfan Utiarahman; Idham Halid Lahay; Rezkiawan Tantawi; Surya Handrisusanto Ahmad (Komisi Pemberantasan Korupsi, 2025)
This study aims to measure the level of the integrity index in the Gorontalo region, which includes six districts/municipalities and one province. Data were collected using a questionnaire instrument distributed to civil servants, beneficiary communities, vendors, and experts. The data were processed using R-Studio software to ensure accurate and comprehensive analysis. The findings reveal significant variations in index scores, with the highest score recorded in Bone Bolango District and the lowest in Pohuwato District. The dimensions of transparency and goods/services procurement management show strong performance, while institutional integrity and anti-corruption outreach tend to be low. Gorontalo City and North Gorontalo District show low institutional integrity scores, indicating the need for organizational culture reform and strengthened oversight systems. Initiatives such as technology-based services, community engagement, and anti-corruption training have shown positive outcomes, although their implementation remains inconsistent. Indications of nepotistic practices and tolerance toward gratuities pose challenges that require immediate attention. Strategic recommendations include strengthening internal oversight mechanisms, implementing a meritocracy system to eliminate nepotism, intensifying anti-corruption outreach, and enhancing community involvement in public oversight. The use of information technology and collaboration with supervisory institutions such as the Corruption Eradication Commission (KPK) are essential to realizing a more integrity-driven, transparent, and accountable governance system in Gorontalo.